2020
DOI: 10.1039/d0ma00687d
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitive hydrogels cross-linked by magnetic LAPONITE® RD®: effects of particle magnetization

Abstract: The work discusses the synthesis and the properties of magnetite modified Laponite® RD platelets (Lap). Magnetized Lap (mLap) nanoparticles were synthesized by a co-precipitation method with different weight ratios X=...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It was stated that this situation is related to the polymer/water interfacial tension. In the study of Lebovka et al, 37 it was observed that the laponite particles are covered by magnetite nanoparticles due to the differences in surface charges, causing the formation of large magnetic particle clusters. Finally, we can say that the increase in particle size of magnetic latexes (LAMP‐2/3/4/5) compared to latex without MNPs (LAMP‐1) indicates that clay/Fe 3 O 4 nanoparticles are encapsulated in polymer particles 27,38 .…”
Section: Resultsmentioning
confidence: 99%
“…It was stated that this situation is related to the polymer/water interfacial tension. In the study of Lebovka et al, 37 it was observed that the laponite particles are covered by magnetite nanoparticles due to the differences in surface charges, causing the formation of large magnetic particle clusters. Finally, we can say that the increase in particle size of magnetic latexes (LAMP‐2/3/4/5) compared to latex without MNPs (LAMP‐1) indicates that clay/Fe 3 O 4 nanoparticles are encapsulated in polymer particles 27,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Modification of Lap particles also resulted in changing of a three-dimensional spatial network in hydrogels. For example, the use of magnetically modified Lap as a physical cross-linking agent allowed us to synthesize magnetic thermosensitive hydrogel nanocomposites with improved mechanical properties and swelling ability, controllable temperature-induced drug release, and demonstrated promise as a nanoplatform for targeted contactless drug delivery under application of weak magnetic fields . Biocompatible and magneto-responsive Lap-based hydrogels with tunable properties were prepared.…”
Section: Introductionmentioning
confidence: 99%